Analysis of International Monetary Fund under conditions of globalization of economic processes - V.V. Ksendzuk (Vìsnik Žitomirsʹkogo Deržavnogo Tehnologìčnogo Unìversitetu: Ekonomìčnì Nauki, 2016)
Globalization in the economy requires proper management of countries' financial resources as the regulation of international financial market is one of the most important tasks of the successful development of the world economy and individual national economies. The International Monetary Fund since the beginning of its creation was intended to regulate the financial situation in the post-war period in world space. In present conditions of information development of the world economic system the role and importance of international financial institutions are changing. Thus, the policies and activities of the IMF are increasingly criticized, that is substantiated and requires some restructuring and reforming areas of the Fund activity. During the research the basic aspects of IMF activities in 2015 have been analyzed and the suggestions for its further effective development have been presented. In particular, it is advisable to use the specific individual approach to the problems of particular economies and to view the sizes of quotas and their functional purposes that will allow to develop new funding mechanisms that are based on social and ecological needs of society. This, in turn, will reduce the impact of developed countries on the activities of the financial institution